2020
DOI: 10.3390/ijms21041374
|View full text |Cite
|
Sign up to set email alerts
|

OmixLitMiner: A Bioinformatics Tool for Prioritizing Biological Leads from ‘Omics Data Using Literature Retrieval and Data Mining

Abstract: Proteomics and genomics discovery experiments generate increasingly large result tables, necessitating more researcher time to convert the biological data into new knowledge. Literature review is an important step in this process and can be tedious for large scale experiments. An informed and strategic decision about which biomolecule targets should be pursued for follow-up experiments thus remains a considerable challenge. To streamline and formalise this process of literature retrieval and analysis of discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The core of humanistic spirit is human consciousness, just as the core of modern consciousness is human consciousness. As a modern man, he must have a conscious human consciousness, that is, the humanist spirit of people-oriented [10]. Studying the literature curriculum from the perspective of curriculum theory and putting the selection and determination of literature curriculum into a process of curriculum design will help to observe the selection of literature curriculum from the perspective of literature curriculum objectives.…”
Section: Introductionmentioning
confidence: 99%
“…The core of humanistic spirit is human consciousness, just as the core of modern consciousness is human consciousness. As a modern man, he must have a conscious human consciousness, that is, the humanist spirit of people-oriented [10]. Studying the literature curriculum from the perspective of curriculum theory and putting the selection and determination of literature curriculum into a process of curriculum design will help to observe the selection of literature curriculum from the perspective of literature curriculum objectives.…”
Section: Introductionmentioning
confidence: 99%
“…The associated proteins were further categorised as potential interaction partners with LIN28A (line type): direct protein-protein interaction with LIN28A (Parisi et al, 2021) as mRNA targets of LIN28A (Hafner et al, 2013). Additionally, we used a literature miner pipeline (modified version (Steffen et al, 2020)) to evaluate the background knowledge of these proteins associated with the keyword "cortical development". The proteins were assigned into three categories: 1 = at least one review article; 2 = at least one research article; 3 = no literature found (Steffen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…5C) (Hafner et al, 2013;Parisi et al, 2021). We further categorised the proteins using a literature mining tool (modified version (Steffen et al, 2020)) to highlight potential proteins of interest (green colour code in Fig. 5C distinguishing between categories: 1 = at least one review paper/well known, 2 = at least one research paper/known, 3 = no further literature available/not known in context of "cortical development" as keyword (Steffen et al, 2020)).…”
Section: Imbalanced Protein Abundances Associated With a Lissencephal...mentioning
confidence: 99%
“…The tissue distribution of regulated proteins was annotated using the normalized-consensus-transcript-expression-dataset provided by the human protein atlas [ 16 ]. The ECM association of regulated proteins as well as their prognostic value in CRC were investigated by a National Center for Biotechnology Information (NCBI) library-based search using the ‘OmixLitMiner’ tool for literature retrieval [ 17 ] (‘extracellular matrix’ in title or abstract). Afterwards, ECM association was annotated manually.…”
Section: Methodsmentioning
confidence: 99%